2020
DOI: 10.1016/j.cjtee.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Global road traffic injury statistics: Challenges, mechanisms and solutions

Abstract: High-quality data are the foundation to monitor the progress and evaluate the effects of road traffic injury prevention measures. Unfortunately, official road traffic injury statistics delivered by governments worldwide, are often believed somewhat unreliable and invalid. We summarized the reported problems concerning the road traffic injury statistics through systematically searching and reviewing the literature. The problems include absence of regular data, under-reporting, low specificity, distorted cause s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 6 publications
0
33
0
10
Order By: Relevance
“…According to the World Health Organization (WHO), the number of deaths by RTAs continues to rise steadily leaping from 1.15 million in 2000 to 1.35 million in 2018 [ 4 ]. During the year 2018 around 56.9 million deaths occurred worldwide and RTIs account for around 2.37% of them [ 5 ]. RTIs are also one of the top three causes of death for people aged between 5 and 44 years, and the leading cause of death for young people between the ages of 5 and 29 years [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization (WHO), the number of deaths by RTAs continues to rise steadily leaping from 1.15 million in 2000 to 1.35 million in 2018 [ 4 ]. During the year 2018 around 56.9 million deaths occurred worldwide and RTIs account for around 2.37% of them [ 5 ]. RTIs are also one of the top three causes of death for people aged between 5 and 44 years, and the leading cause of death for young people between the ages of 5 and 29 years [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…RTAs also have a significant impact on the global economy because in most cases economically productive population are subject to it due to the need for extensive travel and mobility [ 11 ]. Unfortunately, official RTIs statistics worldwide are often believed to be slightly inaccurate due to reporting problems including the absence of regular data, under-reporting, inconsistency, inaccessibility, and delay of data release [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO) data, it was found that in 2016, approximately 1.4 million people lost their lives due to road accidents and that number is likely to increase [4], [5], [6]. The WHO must set an agenda of safety practices for road accidents by focusing on member countries to reduce mortality from road accidents to 50% in the 2020-2030 [7]. Road traffic injuries are now the leading cause of death for children and young adults aged 5-29 years of age in low-income countries which account for about 10% of the world's population [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO must set an agenda of safety practices for road accidents by focusing on member countries to reduce mortality from road accidents to 50% in the 2020-2030 [7]. Road traffic injuries are now the leading cause of death for children and young adults aged 5-29 years of age in low-income countries which account for about 10% of the world's population [7], [8], [9]. The countries in these group have small number of vehicles used (less than 1% of worldwide).…”
Section: Introductionmentioning
confidence: 99%
“…Установление механизма криминальной, в частности автомобильной травмы -одна из основных задач судебно-медицинской экспертизы [1]. При высокоэнергетической пешеходной травме нижних конечностей [2,3] под действием кинетической энергии значительной величины движущегося транспортного средства (ТС) образуются переломы длинных костей, характер смещения фрагментов которых позволяет определить направление действия и величину травмирующей силы [4,5]. В таких случаях результаты криминалистической и автотехнической, в том числе транспортно-трасологической, экспертиз, как правило, подтверждают наличие при-знаков следового контакта пешехода с транспортным средством, выявляют индивидуальные особенности строения совершившего наезд автомобиля и последовательность следов, которые образованы ТС на месте дорожнотранспортного происшествия (ДТП), что в конечном итоге позволяет установить механизм ДТП в каждом конкретном случае [6,7].…”
Section: Introductionunclassified